Leadership in a Public Goods Experiment with Permanent and Temporary Members - Vera Angelova; Werner Güth; Martin G. Kocher (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2019)
We experimentally analyze leading by example in a public goods game with two permanent and two temporary group members. Our results show that leadership when permanent and temporary members interact leads to lower contributions than interaction without leadership.
Keywords: C91; D03; D64; 330; Cooperation; leadership; social dilemma; public goods provision; experiment